Development Of A Wearable Ankle Rehabilitation Device For Patient With Calf Muscles Flexibility Problems - Md. Rozali, Sahazati; Tan, Yi Lin; Che Amran, Aliza; Kamarudin, Muhammad Nizam (University of El Oued, 2018)
This paper presents the development process and analysis of a wearable ankle rehabilitation device designed for patient with calf muscles flexibility problems.The device is used to help patient in exercising the ankle to strengthen,lengthen and maintain the calf muscles.By using a joystick module to control the actuation of the servo motor,the ankle brace moves the ankle to plantar flexion and dorsiflexion movements.Besides that,MyoWareTM Muscle Sensor is used to generate electromyography (EMG) signal from the calf muscles to monitor the servo motor. Exercising the ankle frequently can increase the calf muscles flexibility.The robotic ankle brace device accommodates the robot-guided at-home therapy requirements and is user-friendly.This allowed patient to perform exercise on the ankle more frequent and the recovery process can be reduced effectively.Other than being used as a treatment,this ankle brace is suitable for daily exercise too.